Solid Waste management during warehouse racking installation inn paglima garang site / Nor Fadilah Nasaruddin - Nor Fadilah , Nasaruddin (2019)
An effective solid waste management in warehouse racking installation is very necessary to avoid related impacts on workers health and environmental. Current practice of solid waste management in warehouse racking installation is a challenge that must be planned, handled properly and safely. Strategies to control the solid waste generation from the first process until end process are among the best and appropriate way must be applied. Control over the generation of solid waste can help to reduce solid waste being sent to landfill. Therefore, it is significant to study how to improve solid waste strategy and control in warehouse racking installation process. Research has been proven that waste generation increased by 3% annually due to many causes such as urban migration, affluence and rapid development. Therefore, this research is focusing on how to improve solid waste strategy and control in warehouse racking installation process. This due to reduce the solid waste generated being sent to landfill and implement waste hierarchy as known as 3R (reduce, reuse, recycling). Besides that, avoid the negative impacts on workers health and environment due to ineffective solid waste management method. There are several methods used to conduct this research included; the observation through the site visit responded by staffs through questionnaire given and reviews through journals and books. From the finding indicates that wastes generated during the warehouse racking installation werenï¿½t disposal properly. There are some recommendations for encourage workers participate in managing solid waste during warehouse racking installation. The best practice to do is by expose workers the benefits of managing solid waste and keep inform them the negative effects of solid waste on workers health and environment when poor managing solid waste is apply in workplace.